Improved physiological defense responses by application of sodium nitroprusside in Isatis cappadocica Desv. under cadmium stress. Issue 1 (30th October 2020) - Souri, Zahra; Karimi, Naser; Farooq, Muhammad A.; da Silva Lobato, Allan K.
Abstract: Isatis cappadocica is a well‐known arsenic‐hyperaccumulator, but there are no reports of its responses to cadmium (Cd). Nitric oxide (NO) is a signaling molecule, which induces cross‐stress tolerance and mediates several physio‐biochemical processes related to heavy metal toxicity. In this study, the effects of Cd and sodium nitroprusside (SNP as NO donor) on the growth, defense responses and Cd accumulation in I. cappadocica were investigated. When I. cappadocica was treated with 100 and 200 μM Cd, there was an insignificant inhibition of shoot growth. However, Cd stress at Cd400 treatment decreased significantly the dry weight of root and shoot by 73 and 38%, respectively, as compared to control. The application of SNP significantly improved the growth parameters and mitigated Cd toxicity. In addition, SNP decreased reactive oxygen species (ROS) production induced by Cd. The increased total thiol and glutathione (GSH) concentrations after SNP application may play a decisive role in maintaining cellular redox homeostasis, thereby protecting plants against oxidative damage under Cd stress. Bovine hemoglobin (Hb as NO scavenger) reduced the protective role of SNP, suggesting a major role of NO in the defensive effect of SNP. Furthermore, the reduction in shoot growth and the increase of oxidative damage were more severe after the addition of Hb, which confirms the protective role of NO against Cd‐induced oxidative stress. The protective role of SNP in decreasing Cd‐induced oxidative stress may be related to NO production, which can lead to stimulation of the thiols synthesis and improve defense system.